Study of Living Hadith on the Reading Tradition of Ya Tarim Wa Ahlaha as a Media for Tawasul among the Banjar Society - Akhmad Sagir; Hanafi Hanafi (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
The meaning of the concept of tawassul shows various forms of traditions that developed in Banjarese society. One of its forms is the reading of ya Tarim wa ahlaha which is widely found in various circles. The forms of experience are varied, the first is read as a prayer in a congregation or read privately, the second is written and pasted in various places, such as restaurants, shops, and other business places to make the business smooth, in demand, and given convenience with the wasilah reading. This study aims to reveal aspects of living hadith in the experience of this tawassul practice in Banjarese society. This research uses ethnographic methods that are descriptive-qualitative. The purpose of this method is to understand other ways of life from the point of view of society. The data collection studies used are using observation, interviews, and documentation using an anthropological approach. This approach is important to use in the study of living hadith to make it easier for researchers to photograph as they are about the dimensions of beliefs, beliefs, rituals, and traditions holistically, and not to lead researchers to justify a practice that is being carried out by society.